A CLINICAL CASE OF PARAURETHRAL GLAND ADENOCARCINOMA - Новикова, Оксана Николаевна; Петрич, Любовь Никитична; Фетищева, Лариса Егоровна (Mother and Baby in Kuzbass, 2025)
Adenocarcinoma of the paraurethral glands is a very rare neoplasm of the urinary tract. Due to the rarity of this disease, there is no standard therapeutic approach. We report a case of paraurethral gland adenocarcinoma in a 56-year-old woman with abnormal serous vaginal discharge. X-ray examination revealed a 5 cm-sized formation around the urethra, which underwent surgical resection. Histological examination revealed a moderately differentiated adenocarcinoma, probably originating from the paraurethral glands. Further observation of the patient revealed a recurrence of the process with metastasis along the lymphatic pathways. The publication of this case aims to draw attention to the possibility of oncological damage to the skin gland in patients with long-term inflammatory processes of the urinary tract in postmenopause. When visualizing the bulky formation of the anterior vaginal wall, adenocarcinoma of the Skin gland cannot be excluded. To determine the correct treatment tactics and follow-up of this category of patients, the intervention of an oncologist is necessary.